Flight Phase-Based Analysis of Electrical Load and Generator Performance in Boeing 737-500 Using Flight Test Data - Andy Marjono Putranto; Sovian Aritonang; Erzi Agson Gani; Lalu Aan Sasaka Akbar; Ani Widuri (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study analyzes electrical load behavior and engine-driven generator performance on the Boeing 737-500 using real flight test data across all flight phases, including taxi, takeoff, climb, cruise, descent, approach, and landing. The analysis is based on operational parameters such as altitude, airspeed, N1, N2, EGT, fuel flow, oil pressure, oil temperature, and vibration. Results show that the highest electrical loads occur during takeoff and climb due to anti-ice operation, bleed air demand, and maximum thrust settings, while the cruise phase at FL350 provides the most stable operating condition with balanced load distribution and minimal frequency fluctuation. Moderate load changes occur during descent as system configurations transition. Overall, generator performance remains stable throughout all flight phases without imbalance or frequency deviation. Unlike previous simulation-based studies, this research provides empirical evidence from actual aircraft operations, contributing to condition-based maintenance development and aircraft electrical system monitoring frameworks.